Fruit Quality of Sweet Cherry Cultivars Grafted on Four Different Rootstocks - Simon, G.; Hrotkó, K.; Magyar, L. (International Journal of Horticultural Science, 2004)
A rootstock trial planted at the Szigetcsep experimental station in 1989 involved the study of two cultivars- `Germersdorfi FL 45' and 'Van' -grafted on four different rootstocks — 'Colt', `MxM 14 — Brokforest', `MxM 97 — Brokgrow' and 'Saint Lucie 64' as a control. The trees were trained to the "Modified Brunner-spindle" system and came into bearing in 1993. The yield per tree, fruit weight and fruit diameter have been measured each year since then. The refractivity, the acid content of the fruit juice, fruit cracking after four hours' dipping in water and stone weight ratio have also been measured since 1995. In 1997 and 1998 these parameters as well as fruit cracking after 24 hours' dipping were measured. Fruit firmness and fruit colour were also estimated. In almost every observed parameter significant differences were found between the scion cultivars. Yield efficiency was significantly higher on 'NUM 14' and 'Saint Lucie 64' than on the other two rootstocks. As regards fruit weight, in both cultivars and over an average of six years, it was found that trees on low yielding tree on 'Colt' rootstock had the highest fruit weight values and on heavy producing `MxM 14' the smallest. Soluble solids content was higher on 'Colt' and `MxM 97'. No significant differences between the rootstocks were found in acid content of the fruit juice. There were significant differences between the rootstocks in fruit cracking after 4 and 24 hours' dipping in water. Seemingly with respect to cultivars and rootstocks the year has a considerable effect on fruit cracking.